Physical training of young biathletes in step preliminary preparation - Burla, Artem A.; Burla, Anton A.; Kudrenko, A.I.; Liannyi, M.O. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose : To examine the effectiveness of different allocation of general and special physical training of young biathletes in the preparatory and competitive periods of the annual cycle at the stage of preparation. Material : The study included 24 young athletes (age 13-15 years, have been employed 1 year or more). Results : shows dynamics of the various components of fitness of young biathlon (running at 30 meters from the place of 1000 and 3000 meters, pulling up on crossbeam flexion and extension hand in the emphasis lying down, raising and lowering legs Wies, long jump with space shuttle run 4 x 9 meters). Recommended for general physical training in the preparatory period allocate 65% of the time, a special and comprehensive training - 35%. Time on general fitness is distributed as follows: Power - 50% of the time, speed and speed-power - 25%, the development of general and special endurance - 20%, improving flexibility and coordination skills - 5%. Conclusions : lessons for biathlon in the early years of training should not be aimed at increasing the level of general and special endurance. In more classes should be directed at improving the physical fitness of versatile, high-speed, speed-strength and power qualities of athletes.